BEBERAPA PENCIRI BERBASIS SEKUENS UNTUK MENGENALI SIFAT FUNGSIONAL PEPTIDA BIOAKTIF: STUDI EKSPLORASI - Badrut Tamam; Dahrul Syah; Hanifah Nuryani Lioe; Maggy T. Suhartono; Wisnu Ananta Kusuma (Jurnal Teknologi dan Industri Pangan, 2018)
Bioactive peptides have important role as functional food ingredients. The sequence patterns of amino acids in peptide fragments may relate to their functional mechanisms. On the contrary, presence of an amino acid in a peptide fragment might not be sufficient to provide a unique identifier toward the bio-active peptide functional properties as antihypertensive (AH), antioxidative (AO) or antimicrobial (AM) agents. The main objective of this study was to explore the identifiers of bioactive peptides based on the sequence-generated properties. This study was performed using meta-analysis by utilizing many data sources and qualified international journal publications. The identifiers of bioactive peptides include sequence length, molecular weight, isoelectric point (pI), net charge and hydrophobicity. Based on the average score of the five identifiers, antimicrobial (AM) peptides were very different from antihypertensive (AH) and antioxidative (AO) peptides. The comparisons of the peptide biofunctional properties based on the identifiers may be determined as follows: AH1<AO1<AM1 (for sequence length); AH1<AO1<AM1 (for molecular weight); AH1=AO1<AM1 (for isoelectric point/pI); AH1=AO1<AM1 (for net charge) and AH1<AM1<AO1 (for hydrophobicity).